The Logic of Aboriginal Rights - Ivison, Duncan (Ethnicities, 2003)
Are there any aboriginal rights? If there are, then what kind of rights are they? Are they human rights adapted and shaped to the circumstances of indigenous peoples? Or are they specific cultural rights, exclusive to members of aboriginal societies? In recent liberal political theory, aboriginal rights are often conceived of as cultural rights and thus as group rights. As a result, they are vulner- able to at least three kinds of objections: i) that culture is not a primary good relevant to the currency of egalitarian justice; ii) that group rights are inimical to the moral individualism of liberal democratic societies; and iii) that pandering to group interests provides incentives for abuse and undermines the conditions required for promoting liberal egalitarian outcomes. My argument is that a success- ful defense of aboriginal rights will tie them to the promotion of the equal freedom of aboriginal people, both in the formal and substantive senses, and thus to improve- ments in their actual wellbeing, both as ‘peoples’ and individuals. But rights and norms interact in complex ways, and the translation of particular individual and social goods into the language of rights is always fraught with difficulty